Evaluación de la respuesta dinámica del subsuelo en depósitos volcánicos y sus implicaciones para el diseño sísmico - Yamin, Luis E.; Caicedo, Bernardo; Solano, Erick (Revista de Ingeniería, 1999)
The presence of superficial soils of volcanic origin and large man made fills of varying materials, which are supported by more competent soils, is a general characteristic of the Colombian Coffee Growing Region. This paper present results from laboratory tests performed on unaltered samples of volcanic ash soil, the typical ranges of dynamic properties observed and the variation of shear modulus and associated damping with level of strain. It also evaluates the expected dynamic response of representative deposits and presents the results of sensibility analysis of relevant variables. The dynamic response is compared with one of the available accelerographic records for the January 25th, 1999 Armenia Earthquake, and the design spectra is proposed for areas with different characteristics.